Bromodomain Containing Protein 4 (BRD4) Regulates Expression of its Interacting Coactivators in the Innate Response to Respiratory Syncytial Virus - Xu, Xiaofang; Mann, Morgan; Qiao, Dianhua; Li, Yi; Zhou, Jia; Brasier, Allan R. (Frontiers in Molecular Biosciences, 2021)
Bromodomain-containing Protein 4 (BRD4) plays a central role in coordinating the complex epigenetic component of the innate immune response. Prior studies implicated BRD4 as a component of a chromatin-modifying complex that is dynamically recruited to a network of protective cytokines by binding activated transcription factors, polymerases and histones to trigger their rapid expression via transcriptional elongation. Our previous work extended our understanding of the airway epithelial BRD4 interactome by identifying over 100 functionally important coactivators and transcription factors whose association is induced by respiratory syncytial virus (RSV) infection. RSV is an etiological agent of recurrent respiratory tract infections associated with exacerbations of chronic obstructive pulmonary disease. Using a highly selective small-molecule BRD4 inhibitor (ZL0454) developed by us, we extend these findings to identify the gene regulatory network dependent on BRD4 bromodomain (BD) interactions. Human small airway epithelial cells were infected in the absence or presence of ZL0454 and gene expression profiling was performed. A highly reproducible data set was obtained that indicated BRD4 mediates both activation and repression of RSV inducible gene regulatory networks controlling cytokine expression, interferon (IFN) production and extracellular matrix remodeling. Index genes of functionally significant clusters were validated independently. We discover that BRD4 regulates expression of its own gene during the innate immune response. Interestingly, BRD4 activates expression of NFkB/RelA, a coactivator that binds to BRD4 in a BD-dependent manner. We extend this finding to show BRD4 also regulates other components of its functional interactome, including the Mediator (Med) coactivator complex, and the SWI/SNF Related, Matrix Associated, Actin Dependent Regulator Of Chromatin (SMARC) subunits. To provide further insight into mechanisms for BRD4 in RSV expression, we mapped 7,845 RSV-inducible Tn5 transposase- peaks onto the BRD4-dependent gene bodies. These were located in promoters and introns of cytostructural and extracellular matrix (ECM) formation genes. These data indicate that BRD4 mediates the dynamic response of airway epithelial cells to RNA infection by modulating expression of its coactivators, controlling expression of host defense and remodeling genes through changes in promoter accessibility.